THE DUAL PILLARS OF ENGINEERING EDUCATION: EMPHASIZING IDEOLOGICAL AND POLITICAL LEARNING IN VOCATIONAL SETTINGS - Li , Wang Xiao; Feng , Liu Hua (Research Journal of Education and Allied Studies, 2024)
In vocational engineering courses, ideological and political education plays a pivotal role in fostering students' moral values and awareness of legal norms. This is achieved by encouraging students to analyze moral issues, emphasizing the significance of moral standards, and enhancing their moral sensitivity and responsibility. Additionally, the study of reallife cases helps students comprehend the interconnectedness of morality and legality, subsequently elevating their legal awareness and competence. This approach facilitates the effective cultivation and reinforcement of students' moral virtues, contributing to their holistic development.